2008
DOI: 10.1080/01635580802196107
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Low Selenium Levels in Adult Patients Undergoing Bone Marrow Transplantation: A Brief Communication

Abstract: Selenium (Se) is an essential trace element, and its deficiency is considered to be important in various types of cancer. There are just a few data regarding this issue among adult patients with hematological malignancy. Serum Se levels were determined in 22 adult patients candidates for bone marrow transplantation (BMT) in Iran. The mean serum Se levels before BMT was 19.91 microg/l (from 12.00 to 62.00 microg/l), and almost all the patients had low Se serum levels (normal serum Se level: 46-143 microg/l). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Selenium has been linked to the pathophysiology of a diverse set of conditions (e.g., depression, atherosclerosis, and cancer) [ 15 ]. In 1969, populations with an increased selenium intake were found to have a decreased cancer incidence and thus paved the way for research into the therapeutic benefit of selenium [ 116 , 117 ]. Additional evidence suggested that selenium could be useful in cancer treatment and prevention [ 56 , 118 , 119 ].…”
Section: Role Of Selenium and Its Therapeutic Advantages In Various C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium has been linked to the pathophysiology of a diverse set of conditions (e.g., depression, atherosclerosis, and cancer) [ 15 ]. In 1969, populations with an increased selenium intake were found to have a decreased cancer incidence and thus paved the way for research into the therapeutic benefit of selenium [ 116 , 117 ]. Additional evidence suggested that selenium could be useful in cancer treatment and prevention [ 56 , 118 , 119 ].…”
Section: Role Of Selenium and Its Therapeutic Advantages In Various C...mentioning
confidence: 99%
“…Multiple reports have demonstrated a relationship between low serum selenium levels and various hematological malignancies or solid tumor type cancers [ 13 , 14 , 185 , 186 , 187 , 188 ]. Hadjibabaie and co-workers found that twenty-two adult patients with hematological malignancies (Hodgkin disease, ALL, AML, CML, and non-Hodgkin’s lymphoma) had low mean selenium serum levels (19.91 μg/L, from 12.00 to 62.00 μg/L) prior to bone marrow transplantation (BMT) [ 117 ]. Aggressive non-Hodgkin’s lymphoma patients were studied, and it was found that the serum selenium concentration upon diagnosis can be independently related to their prognosis (e.g., treatment response and survival) [ 189 ].…”
Section: Selenium Reduces Disease Progression In Blood Cancersmentioning
confidence: 99%
“…[15][16][17] We have formerly shown that selenium deficiency exists in almost all the patients undergoing HSCT in our institution. 18 Therefore, we decided to evaluate the efficacy of selenium intake for prevention of OM in patients with hematologic malignancies candidate for allogeneic HSCT after receiving HDC. To the best of our knowledge, this is the first investigation regarding the use of selenium administration in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Taking cues from our previous research that has indicated the ability of Se at supraphysiological levels to inhibit the viability of CML LSCs (Gandhi et al 2014) involving the endogenous CyPGs as well as the eicosanoid class switching paradigms (Finch et al 2017), we have embarked on targeting the self-renewing and drug resistant LSCs that are responsible for the postremission relapse of AML to achieve the eradication of LSCs as our goal to treat AML using new paradigms. In support of the role of Se therapy in AML, several studies have reported significantly decreased serum levels of Se were observed in patients with AML, CML, acute lymphoblastic leukemia (ALL), and acute nonlymphocytic leukemia (ANLL) (Pazirandeh et al 1999;Hadjibabaie et al 2008;Khanna et al 2010;Stevens et al 2011). These observations imply an inverse causality between serum levels of Se and the progression of hematopoietic malignancies.…”
Section: Cancer Immunity-mentioning
confidence: 92%
“…4). Previous clinical studies have emphasized the importance of measurement of baseline Se levels in patients, which is a useful guideline for Se intake (Pazirandeh et al 1999;Hadjibabaie et al 2008;Khanna et al 2010;Stevens et al 2011). However, none of the clinical studies, including the SELECT (Selenium and Vitamin E Cancer Prevention Trial) for prostate cancer, have considered the NSAIDs as a confounding factor to explain if the health benefits of Se supplementation are associated with prostanoids.…”
Section: E the Role Of Txa 2 In Immunitymentioning
confidence: 99%